The transfer hydrogenation of high concentration levulinic acid to γ-valerolactone catalyzed by glucose phosphate carbamide zirconium. Issue 9 (22nd April 2021) - Wan, Feifei; Yang, Bo; Zhu, Jiekun; Jiang, Dabo; Zhang, Huanhuan; Zhang, Qiao; Chen, Shuainan; Zhang, Chao; Liu, Yachun; Fu, Zaihui
Abstract : Newly constructed glucose phosphate carbamide zirconium (GluPC-Zr) is an inexpensive, excellent, and recyclable CTH catalyst for the synthesis of γ-valerolactone (γ-GVL) using high concentrations of levulinic acid (LA ). Abstract : Zr-Based catalysts have been extensively applied in Meerwein–Ponndorf–Verley type catalytic transfer hydrogenation (CTH) reactions, but they are easily deactivated in the CTH conversion of high concentrations of levulinic acid (LA) to γ-valerolactone (γ-GVL). This work discloses that by using cheap glucose and ZrCl4 as two main raw materials, glucose phosphate carbamide zirconium (GluPC-Zr) is easily synthesized at large scale and low cost via a simple two-step conversion. The constructed GluPC-Zr has enhanced Lewis acid–base properties and good porosity, thus exhibiting outstanding activity for the CTH reactions of LA or its esters with isopropanol (IPA), providing 95–98% γ-GVL yields. Because of the excellent esterification performance of the introduced acidic phosphate groups, GluPC-Zr also works well at high LA concentrations, achieving a much higher turnover frequency (TOF, 8.2 mmol γ-GVL per g catalyst per h) than previously reported Zr-based catalysts (TOF, 0.2–2.4). And it shows excellent reusability in the reaction of LA with IPA, still providing ca. 95% γ-GVL yield after the seventh cycle run. This work provides a preferential esterification strategy for LA to hamper catalyst deactivation, which is of special significance for the large-scale production of γ-GVL from biomass-derived LA and a low-cost GluPC-Zr catalyst.